Local autologous platelet rich plasma injection combined with platelet rich fibrin filling as the main treatment for refractory wounds: A case series - Liu, Xiang; Li, Xiangjun; Wei, Wei; Zhang, Xiang; Fang, Zheng; Chen, Zixiu; Chen, Pingxiang; Li, Haihong (Frontiers in Surgery, 2023)
Refractory wounds are a major global health problem that not only affects the quality of life, but also causes significant physical, psychological and economic burdens. How to promote wound healing has become the main goal of clinicians. To evaluate the safety and efficacy of local autologous platelet rich plasma (PRP) injection combined with platelet rich fibrin (PRF) filling as the main treatment for refractory wounds. In the study, autologous PRP and PRF were prepared from whole blood. Twelve patients, each having a refractory wound, were included. The wounds were debrided first to remove necrotic and infected tissues, and then were given once or twice local PRP injection combined with PRF filling treatment. The total healing time (the time from admission to wound healing) and the healing time after PRP/PRF combined treatment (the time from PRP treatment to wound healing), as well as the adverse events were recorded. The results showed that the wound duration before the combination treatment was 10.48  3.66 weeks, and the mean area/volume (for sinus or fistula) of the wounds was 8.23  2.67 cm2/9.54  2.13 cm3 (for sinus or fistula). All wounds healed after once or twice PRP/PRF combined treatment. The total healing time was 26.91±8.01 days, and the healing time after the combined treatment was 16.36±7.47 days. No adverse events were reported during the treatment and follow-up period. Our case series demonstrate the safety and synergistic effectiveness of local autologous PRP injection combined with PRF filling as the main treatment for refractory wounds. Platelet concentrates is not only an adjuvant treatment for chronic wounds, but a potential substitute for chronic wounds, especially in sinuses and fistulas.